Les quais nos 1, 12 et 13 du port romain de Saint-Lupien à Rezé/Ratiatum (Loire-Atlantique) - Xavier Favreau; Nicolas Ménez (Gallia)
In the final years of the 1st c. AD the riverbank of the Saint-Lupien district in Rezé/Ratiatum (Loire-Atlantique) was the object of an ambitious urban planning program that transformed it, subsequently emerging as a structured and monumental constructed space. The bank of the Loire was thus punctuated, and then divided into several construction modules built according to timber box construction guidelines and serving as docks. Excavated simultaneously with the box no. 9, the most complete, the two ensembles composed of boxes nos. 12, to the west, and nos. 1 and 13, to the east, were only partially observed through the excavation of small test trenches within each box. Though limited in scope, these trenches were sufficient to underscore the singularity of their construction materials. Box no. 12 is positioned obliquely relative to the edge of the riverbank and presents a shape that can probably best be restored as a non-rectangular parallelogram. This form breaks in a singular way with the regular frame tradition observed elsewhere. Boxes nos. 1 and 13 present a rectangular form and seem to mark the end of the riverbank constructions toward the upstream portion of the river. These works –which ensue from the first embankment structures mounted on posts– were initially all composed of a sturdy oakwood frame mixed with a solid stone infill. Their facades, built following the model of a timber framework system, bear witness to a process rarely attested to for the Roman world in a harbor context. Their state of preservation is remarkable and despite varying degrees of legibility from one box to another, it has allowed for the observation of an entire series of traces left by the carpenters and for the reconstruction of the operational chain of construction for the docks. The apparent and general similarity of the wooden frames of the boxes excludes neither the presence of singularities in their individual implementation, nor does it prohibit individualities in the assembly techniques employed. Variations have been observed which imply the coexistence of several carpentry and masonry workshops, and which also suggest the existence of several construction campaigns. Moreover, the dendrochronological analysis confirms a homogeneity within the dating for each set and a spread of construction work along the riverbank, which would appear to develop from west to east. The subsequent transformations of each ensemble, materialized by major restructuring, as well as the association or overlay of new timber boxes, signal the transition from a mixed construction comprised of wood and stone, to the exclusive use of the latter material toward the middle of the 2nd c. AD. This common architectural development testifies to a gradual retreat from the shoreline toward the north and suggests a desire, despite this, to maintain port activity and access to the river. This tiering of monumental port terraces, which developed, operated and was modified, only functioned for about a century. Initiated in the first half of the 3rd c. AD, the gradual backfilling of the base of the riverbank slope marks the definitive abandonment of the docks in their monumental form, in the face of the worsening hydrological crisis. This form would eventually be replaced by the installation of a gently sloped slipway established overtop of these destroyed structures.